2001
DOI: 10.1074/jbc.m107664200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Apoptosis by Vitamin C

Abstract: We have investigated the ability of intracellular vitamin C to protect human umbilical vein endothelial cells from exposure to hypochlorous acid (HOCl) and a range of derived chloramines. Ascorbate provided minimal protection against the cytotoxicity induced by these oxidants, as measured by propidium iodide uptake. In contrast, there was a marked effect on apoptosis, monitored by caspase-3 activation and phosphatidylserine exposure. Extended incubation of the cells with glycine chloramine or histamine chloram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…[47] Vissers et al reported that intracellular ascorbate can specifically protect apoptosis in human umbilical vein endothelial cells (HUVEC) in the presence of chlorinated oxidants. [48] In the present study, a significant decrease in the severity of histopathological and morphometric changes induced by cisplatin was observed in rat kidney treated with vitamin C plus cisplatin when compared with the cisplatin group.…”
Section: Discussionmentioning
confidence: 66%
“…[47] Vissers et al reported that intracellular ascorbate can specifically protect apoptosis in human umbilical vein endothelial cells (HUVEC) in the presence of chlorinated oxidants. [48] In the present study, a significant decrease in the severity of histopathological and morphometric changes induced by cisplatin was observed in rat kidney treated with vitamin C plus cisplatin when compared with the cisplatin group.…”
Section: Discussionmentioning
confidence: 66%
“…It has been demonstrated that the apoptosis-inducing activity of ascorbate in human myelogenous leukemic cell lines is abrogated by catalase, implicating the involvement of hydrogen peroxide [56]. However, studies by Vissers et al [57] in human umbilical vein endothelial cells treated with chlorinated oxidants showed that although ascorbate (1mM) was ineffective at preventing glutathione oxidation or protecting against the cytotoxicity of these agents, it appeared to protect the apoptotic machinery from oxidant damage, allowing progression of apoptosis over necrosis. Here, we have demonstrated a similar but more modest effect in macrophages, even in the presence of catalase and using a 10-fold lower and more physiologically relevant concentration [58] of ascorbate.…”
Section: Discussionmentioning
confidence: 86%
“…The oxidative process helps exposure of phosphatidylserine on antibody-damaged neutrophils, so that they are phagocytosed [83]. Yet actually chloramine dampens this process [84] and could explain the impaired neutrophil clearance [85], which will mean that antigens could persist to induce autoantibody formation. However, excessive ROS production by neutrophils can also lead to hyporesponsive T lymphocytes [86].…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%